Essentials of nursing practice - Delves-Yates, Catherine (Los Angeles : SAGE, 2015)
"Essentials of Nursing Practice is a ground-breaking new resource which introduces nursing students to the core topics they need to master during their first year and beyond. It brings the study of nursing to life across all four fields of nursing, in all settings, focussing on what it takes to be the best nurse you can be through person-centred compassionate care. Unlike any other book it uniquely blends digital and print learning resources to engage all styles of learners and to provide lecturers with helpful resources to use in their teaching."--
What is nursing and What is a nurse? -- Being a nursing student -- Core academic skills -- Academic writing and assessment skills -- Ethics -- Law -- Accountability and professionalism -- Resilience -- The role of the nursing student in effecting change -- Clinical governance -- Delivering effective care -- Introduction to nursing theory -- Value-based, person-centered care -- Patient, service user, family and carer perspectives -- assessment, planning, implementation and evaluation (APIE) -- Core communication skills -- Communication and interpersonal skills in challenging circumstances -- Assessing and managing risk -- Record-keeping and documentation -- Clinical decision-making -- Health promotion -- Safeguarding -- Patient education -- Infection prevention and control (IPC) -- Clinical measurement -- Pain management -- Aseptic technique and specimen collection -- Skin integrity -- Safer handling of people -- First aid -- Medicines administration -- Assisting patients with their nutritional needs -- Assisting patients with their elimination needs -- Assisting with their hygiene needs -- Last offices -- Introduction to the organization and settings of care -- Public health -- Introduction to interprofessional working -- Introduction to the psychological context of nursing -- Introduction to the sociological context of nursing -- Introduction to health policy and the political context of nursing -- Introduction to the global context of nursing.
Includes bibliographical references and index.
Keywords: Nursing; Nursing; Nursing Care; Nursing Process; Nursing; Omvårdnad.